Akuntabilitas Laporan Keuangan Lembaga Amil Zakat Dalam Memaksimalkan Potensi Zakat - Siti Nurhasanah (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The aims of this study is to determine the zakat management system and the accountability of the Amil Zakat institution's financial statements in order to be able to maximize the potential of zakat that can be collected. Zakat is the third pillar of Islam that must be fulfilled by all Muslims in the world when it has reached its provisions. Accountability of financial statements is a manifestation of responsibility to society, the state, and Allah. Therefore the Amil Zakat Institution must report the results of zakat management and distribution to Muzakki in order to gain trust from the community so that the potential for zakat collected is much greater because of the public's trust in the Amil Zakat institution. In order for the public's awareness and trust in zakat to become more flourishing, it can be realized through the performance of accountable, transparent and professional Amil Zakat Institutions (LAZ). For this reason, the Amil Zakat institution must have a financial report which is a reflection of good financial management.